MORPHOLOGICAL STRUCTURE OF LATE RENAL GRAFT DYSFUNCTION AND ITS EFFECT FOR LONG-TERM RESULTS - E. S. Stolyarevich; T. R. Zhilinskaya; L. Yu. Artyukhina; I. G. Kim; V. A. Zaydenov; N. A. Tomilina (Вестник трансплантологии и искусственных органов)
Aim: to analyze the frequency of different histological diagnoses and it simpact on graft survival in a cohort of patients with renal allograft dysfunction, and to determine pathology features, infl uencing prognosis.Materials and methods. The data obtained from 1470 biopsies, performed by indication at different time after kidney transplantation (48.8 ± 46.1 months) were analyzed retrospectively according to the Banff 2013 classifi cation. Results. The majority of graft dysfunction episodes were attributed to fi ve causes: acute (26,8%) and chronic (12,4%) rejection; chronic nephrotoxicity of СNI (19,3%), interstitial fi brosis/tubular atrophy (15,8%) and recurrent or de novo glomerulonephritis (10,6%). T-cell-mediated acute rejection and functional disorders were the most often cause of dysfunction during the fi rst year after transplantation (40,5% and 21% respectively) but decreased over time. On the other hand, the frequency of chronic rejection, interstitial fi brosis/tubular atrophy with or without СNI nephrotoxicity and recurrent or de novo glomerulonephritis increased from 13%, 26% and 5,5% at the fi rst year to 26,4%, 35,3% and 22,8% respectively at 8 year after transplantation. Chronic rejection represented a major risk for graft loss – 8-year graft survival did not exceed 5%. The prognosis of acute rejection as well as de novo or recurrent glomerular pathologies was more favorable (38% and 42% respectively). In cases of interstitial fi brosis/tubular atrophy with or without СNI nephrotoxicity 8-year graft survival was slightly lower than in the functional disorders (62% and 76%). In acute rejection prognosis for C4d-positive forms was worse compared to C4d-negative, while in chronic rejection there was no difference between C4d-positive and C4d-negative forms. The features of СNI nephrotoxicity did not infl uence the prognosis of non-specifi c interstitial fi brosis and tubular atrophy.Conclusion. Transplant pathology in patients with allograft dysfunction is heterogeneous and changes over time. Acute and chronic rejection; interstitial fi brosis/tubular atrophy with or without СNI nephrotoxicity and recurrent/de novo glomerular pathology are the most often causes of graft dysfunction, but only rejection (mostly chronic) and glomerular pathology are associated with unfavorable prognosis.